Presepsin as a promising biomarker for early detection of post-operative infection in children - Puspaningtyas, Niken Wahyu; Karyanti, Mulya Rahma; Paramita, Tiara Nien; Sjakti, Hikari Ambara; Putri, Nina Dwi; Tridjaja, Bambang; Yanuarso, Piprim Basarah; Rinaldhy, Kshetra; Yani, Ahmad; Gayatri, Pramita (Frontiers in Pediatrics, 2023)
Background Post-operative systemic inflammation response syndrome (SIRS) is an event that results from surgical trauma, white blood cells contact activation, and intra-surgical bacterial translocation, which is difficult to distinguish from sepsis. Presepsin is a novel biomarker that is increased since the early stages of bacterial infection and can be used to confirm the diagnosis of post-operative infectious complications. This study aimed to investigate the diagnostic performance of presepsin for post-operative infectious complications compared to other well-known biomarkers. Method This cross-sectional study included 100 post-operative patients admitted to Cipto Mangunkusumo National Hospital and Bunda Hospital in Jakarta, Indonesia. The objective was to identify the optimal cutoff and trend of plasma presepsin concentration on the first and third day after surgery and to compare them with other biomarkers. Result Plasma presepsin level was higher in the infection group compared to the non-infection group (median 806.5 pg/ml vs. 717 pg/ml and 980 pg/ml vs. 516 pg/ml on the first and third day, respectively). Presepsin levels tended to increase on the third post-operative day (median + 252 pg/ml) in children with infection. The opposite trend was observed in the non-infection group from the first to the third day (median -222.5 pg/ml). Presepsin delta, a three-day difference between the first and third post-operative day, had the best diagnostic performance compared to other biomarkers (Area Under the Curve 0.825). The optimal cutoff for presepsin delta to diagnose post-operative infection was +90.5 pg/ml. Conclusion Serial assessments of presepsin levels on the first and third days post-surgery and their trends are helpful diagnostic markers for clinicians to detect post-operative infectious complications in children.